1966
DOI: 10.1002/1097-0142(196601)19:1<39::aid-cncr2820190104>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Ano-rectal melanoma

Abstract: The incidence of melanoma of the ano‐rectum is discussed and the authors introduce 17 cases from the records of the Armed Forces Institute of Pathology. The anatomy of the ano‐rectum is described and some features which lead to difficulties are discussed. Of particular interest are the intermingling of squamous and columnar epithelium in the area and the problems of definition of the anal boundaries. Reasons are given for regarding only 2 of the 17 cases as truly rectal. Clinical details confirm the poor progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

1968
1968
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(27 citation statements)
references
References 33 publications
0
26
0
1
Order By: Relevance
“…The other 252 were excluded based on title and abstract review. [6][7][8][9][10][11][12][13] Fourteen studies [6][7][8]10,13,18,20,24,26,28,29,31,32,34 originated from the United States, 10 9,11,12,17,19,23,30,33,36,37 from Europe, 6 21,22,25,35,38,39 from Asia, and 1 27 from South America. Of 63 full-text articles evaluated, 32 were excluded by full-text article review.…”
Section: Literature Search and Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The other 252 were excluded based on title and abstract review. [6][7][8][9][10][11][12][13] Fourteen studies [6][7][8]10,13,18,20,24,26,28,29,31,32,34 originated from the United States, 10 9,11,12,17,19,23,30,33,36,37 from Europe, 6 21,22,25,35,38,39 from Asia, and 1 27 from South America. Of 63 full-text articles evaluated, 32 were excluded by full-text article review.…”
Section: Literature Search and Selected Studiesmentioning
confidence: 99%
“…The design of all 31 studies was retrospective review. 10,17,19,21,23,24,[29][30][31]34,35,37,38 Five studies utilized nationwide database as a source of data.…”
Section: Literature Search and Selected Studiesmentioning
confidence: 99%
“…3,17 The prognosis of patients with rectal melanoma has been reported diversely, but it is generally regarded as pessimistic. 10,18,19 However, according to one report, there was no significant difference between the prognosis of patients with amelanotic melanoma and those with other melanomas of the rectum. 20 Rossetti et al 12 reported a median survival of 20 months in patients treated radically and 4 months in patients treated with palliative surgery.…”
Section: Discussionmentioning
confidence: 98%
“…Mason ve ark. primer rektal MM tanısı için tü-mörün anal girimden en az 4 cm proksimalde yerleşmesinin gerekli olduğunu ifade etmiştir [13]. Bu nedenle erken tanıda rektal muayene ve rektoskopi önem arz etmektedir.…”
Section: Tartışma Ve Sonuçunclassified